Implementation of an Integrated Information System for Construction Services Development to Support Infrastructure Projects at the Public Works Department of Tarakan City - Hadriansa, H; Prayogi, Denis; Fadlan, Muhammad; Fandariansyah, F (IJISTECH (International Journal of Information System and Technology), 2025)
Efficient infrastructure development requires effective management, particularly in developing construction services. The Public Works (PU) Department of Tarakan City faces challenges in overseeing and guiding construction service providers to ensure smooth execution and project quality. This study aims to design and implement an integrated information system using the Scrum method, which supports construction service development, project progress monitoring, contractor data management, and budget supervision. Scrum was chosen to enhance flexibility and collaboration among development teams by allowing the system to be built iteratively and incrementally. The system is designed to improve transparency, efficiency, and accuracy in managing construction projects. The implementation results show that applying the Scrum method in developing the integrated information system has successfully accelerated the verification process, reduced administrative errors, and improved budget control. Additionally, the system has increased project management efficiency, expedited decision-making, and facilitated monitoring and evaluation processes. This study recommends further development and expansion of the system to support more effective construction service development in the future